Basic Fibroblast Growth Factor-Mediated Overexpression of Vascular Endothelial Growth Factor in 1F6 Human Melanoma Cells is Regulated by Activation of PI-3K and p38 MAPK - Dennis Fontijn; Linda J. W. Bosch; Monique C. A. Duyndam; Maria P. A. van Berkel; Maarten L. Janmaat; Epie Boven (Cellular Oncology)
Background: 1F6 human melanoma xenografts overexpressing either the 18 kD (18kD) form or all (ALL) forms of human basic fibroblast growth factor (bFGF) demonstrate an abundant number of microvessels and accelerated growth. We now examined whether bFGF mediates vascular endothelial growth factor (VEGF) expression.